Prevalência e fatores associados à desnutrição e à obesidade abdominal em pacientes em hemodiálise na cidade de Goiânia-Go - FREITAS, Ana Tereza Vaz de Souza (2011)
Introduction: parallel to the malnutrition, overweight, and especially abdominal fat, contribute to worse clinical outcomes in hemodialysis patients. Objective: To assess the prevalence and factors associated with malnutrition and abdominal obesity in hemodialysis (HD) patients. Methodology: cross sectional study with 344 patients over 18 years old. The dependent variables, malnutrition and abdominal obesity were obtained by the subjective global assessment (SGA) and waist circumference, respectively. The independent variables involved socioeconomic, demographic, lifestyle, medical history factors, energy and macronutrients intake. It was calculated the body mass index (BMI) and midarm muscle circumference (MAMC), body fat by the sum of four skinfolds (triceps, biceps, subscapular and suprailiac), serum albumin and creatinine. A statistical package Stata 8.0 was used. Student t test, Mann Whitney, chi-square and multiple Poisson regression, with a hierarchical model were used. The considered the level of significance was < 0.05. Results: the group was composed mostly by males (59,30%), with average age of 49.33 ± 13.76 years old and prevalence of moderate malnutrition in 22.4%, with no statistically significant difference between sexes (p=0,929). Malnourished patients had lower BMI, MAMC, % body fat, serum creatinine, p <0.001 and nPNA (p = 0.001). The following variables remained associated with malnutrition: age of 19 to 29 years (PR = 1.23, CI = 1.06 to 1.43), family income <2 minimum wages (PR = 1.13, CI = 1.01 -1.27), duration on HD ≥ 60 months (PR = 1.08, CI = 1.01 to 1.16), Kt / V ≥ 1.2 (RP = 1.12, CI = 1.03 1.22), caloric intake below 35 kcal / kg / day (PR = 1.22, CI = 1.10 - 1.34) and nPNA<1 (PR = 1.13, CI = 1.05 to 1.21). The prevalence of obesity was 44.77% (n=154). It was more prevalent in women (55.71%) than men (37.25%), p = 0.001. The end result of the multivariate analysis identified four factors independently associated with abdominal obesity in men: age over 40 years (PR = 1.22; 95%CI: 1.09 -1.37), economic class D/E (PR = 0.78, 95%CI: 0.68 - 0.90), duration on hemodialysis between 24 to 59 months (PR = 1.12; 95%CI: 1.001-1.26) and BMI ≥ 25kg/m² (PR = 1.52; 95%CI 1.40 -1.65) and three factors in women: age over 40 years (PR = 1.43; 95%CI:1.27-1.60), protein intake below 1,2 g/kg/day (PR= 1.21; 95%CI= 1.05 - 1.39) and BMI ≥ 25kg/m² (PR=1.37; 95%CI:1.26 1.49). Conclusion: There was a high prevalence of malnutrition and abdominal obesity in the population studied. The age below 29 years, low family income, longer hemodialysis period and inadequate protein and caloric intake were the factors associated with malnutrition. In the abdominal obesity, age over 40 years and overweight were associated in both men and women. In men belonging to lower socioeconomic classes and duration on hemodialysis between 2 and 5 years and women with protein intake below the recommended were also associated with abdominal obesity, emphasizing the importance of nutritional intervention because the inadequate food intake, a modifiable risk factor, was crucial in both situations.